KEAMANAN INFORMASI (INFORMATION SECURITY) PADA APLIKASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DENGAN DEFENSE IN DEPTH - Enggar Novianto; Erik Iman Heri Ujianto; Rianto Rianto (Universitas Nusa Cendana, 2023)
The rapid development of Information Technology (IT) has made IT the most important aspect to meet organizational needs. The existence of IT is believed to be able to provide solutions related to the organization's business processes, so that many organizations offer their resources to increase efficiency by relying on information technology support. Information system security is an internal organizational subsystem tasked with managing the risks associated with computerized information systems. Information system security is the application of international control principles, which are specifically used to trigger problems in information systems. Important information leads to protected information structures, more information is now available from the internet, so information management now includes computer and network technology. The goal of information security is to strengthen business operations and protect against falling business prices by minimizing the risks associated with internal security. The purpose of this study is to understand information security in the implementation of the Personnel Management Information System (SIMPEG) at Sebelas Maret University. The research method used is the application of Defense In Depth to analyze information security, including many layers of security to ensure information security. The results of the descriptive analysis explain that the design and development of SIMPEG pays attention to the principles and aspects of data and information security. However, information security vulnerabilities can occur at the server protection layer, network protection layer, and physical protection layer.